(untitled) (International Journal of Engineering Sciences & Management Research, 2018)
Road Traffic Accidents (TRAs) are a major cause of death and disability around the world. Road accidents are ninth ranked cause of death in the world and the ranking is projected to rise to third by 2020. An estimated 85% of the deaths occur in developing countries where 65% of the deaths are pedestrians, of which 35 % are children. In Kenya over 3,000 people die through road accidents every year, most between ages of 15 and 44 years. The kenya police service and NTSA classify areas of frequent and repeated RTI by sections stretching over 50 kilometers, the study identified and mapped 35 blackspots with GPS coordinates , using the LSEModeling the study found Road Traffic Incident fatalities have steadily increased from 2533 fatalities in 2005 rising in 3149 in 2008 and peaking in 2009 at 4032 fatalities in 2015 the fatalities were 2957, motor private and commercial claims paid by insurance industry were at 6,206,700,000 ksh in 2005 the figure rose to 13,687,327,000 in 2011 and peaked in 2015 at some 25,811,991,000 (ksh,billion) a increase of 400% in economic and fatal life losses from RTI in kenya, the country lost ksh 300 billion 5% of GDP in 2016.The study illuminates limitations that contribute to persistent rise in road crashes annually through economic impact of RTI to individuals and Kenyan economy it also highlight the gaps in the national psyche that relegates this economic impact away from the frontline of County Governments budgetary allocation for effective management of road safety.